EDUCATION AND CULTURE IN THE DAILY PRESS: BETWEEN AFFIRMATION AND MARGINALIZATION - Arsenijević, Jasmina and (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2023)
Starting from the attitude that education and culture play a key role in the progress of every society, this paper deals with the affirmation of these activities through media. Media play an important role in the creation of public awareness and can contribute to the development of public interest and support towards education and culture, but also to their marginalization. The subject of this paper is therefore the presence of education and culture in the front pages of the daily press in Serbia. The goal of the paper is to investigate how much education and culture are present in the discourse of Serbian print media, based on the recording and classification of front page news. The research was conducted from November the 1st 2021 till October the 31st 2022, on daily basis. The analysis covered 10 daily newspapers: Politika, Danas and Dnevnik as quality newspaper, Večernje novosti, Blic and Nova as semi-tabloids and Informer, Kurir, Srpski telegraf and Alo! as tabloids. The results were presented in relation to time, newspapers and title tonality. A combination of qualitative (content analysis) and quantitative methods (descriptive statistical analysis of news frequency) was used. During the observed period, 405 titles were published - 274 about education and 131 about culture. The results of the dynamics and structure of reporting indicate insufficient affirmation of education and culture through print media, as well as the imbalance between neutral and polarized news and reduced level of regular reporting due to acute socio-political events. In order to remove the problem of marginalization of education and culture in social consciousness, systematic efforts in popularization of these topics and a more responsible media policy are needed, in which the professionalism, social responsibility and the enlightening role of the media would be set as priorities.